Beyond lifestyle modification: the role of GLP-1 receptor agonists in treating pediatric obesity - Wen, Hua (Frontiers in Pediatrics, 2026)
Childhood obesity is a global health crisis with limited effective therapies beyond lifestyle modification. This review examines the growing role of glucagon-like peptide-1 receptor agonists (GLP-1 RAs) in the management of pediatric obesity. Simultaneously, this study highlights the critical considerations for clinicians in administering these medications, including long-term safety, efficacy, potential adverse effects, and overall clinical utility. To enhance the effectiveness of GLP-1 RAs in managing pediatric obesity, we propose a comprehensive clinical medication use management process that includes review, screening, combination therapy, education, monitoring, and follow-up. We also present recommendations for policymakers and healthcare systems. In conclusion, GLP-1 RAs represent an emerging therapeutic paradigm for pediatric obesity, demonstrating notable efficacy in weight reduction for adolescents. Ongoing research is needed to determine long-term outcomes, optimal treatment duration, and strategies to ensure broad and equitable access to these therapies.